Rapıd Maxıllary Expansıon In Two Borderlıne Cases - Aslı Ender Telli; Bülent Haydar; Yeşim Şençift (Aytan) (Turkish Journal of Orthodontics, 1993)

(untitled)
Rapid maxillary expansion and non-extraction therapy may be an alternative treatment approach for some borderline cases presenting unilateral or bilateral posterior cross-bite, a good profile balance with accompanying maxillary arch length discrepancy and minimal mandibular crowding. This article is a presentation of two cases treated with this treatment concept.